MG53/TRIM72: multi-organ repair protein and beyond - Wang, Yong-Fei; An, Zi-Yi; Li, Jian-Wen; Dong, Zi-Kai; Jin, Wei-Lin (Frontiers in Physiology, 2024)
MG53, a member of the tripartite motif protein family, possesses multiple functionalities due to its classic membrane repair function, anti-inflammatory ability, and E3 ubiquitin ligase properties. Initially recognized for its crucial role in membrane repair, the therapeutic potential of MG53 has been extensively explored in various diseases including muscle injury, myocardial damage, acute lung injury, and acute kidney injury. However, further research has revealed that the E3 ubiquitin ligase characteristics of MG53 also contribute to the pathogenesis of certain conditions such as diabetic cardiomyopathy, insulin resistance, and metabolic syndrome. Moreover, recent studies have highlighted the anti-tumor effects of MG53 in different types of cancer, such as small cell lung cancer, liver cancer, and colorectal cancer; these effects are closely associated with their E3 ubiquitin ligase activities. In summary, MG53 is a multifunctional protein that participates in important physiological and pathological processes of multiple organs and is a promising therapeutic target for various human diseases. MG53 plays a multi-organ protective role due to its membrane repair function and its exertion of anti-tumor effects due to its E3 ubiquitin ligase properties. In addition, the controversial aspect of MG53's E3 ubiquitin ligase properties potentially causing insulin resistance and metabolic syndrome necessitates further cross-validation for clarity.